Propuesta arquitectónica de un complejo deportivo para personas con situación de discapacidad en Guayaquil - Cayetano González, Lourdes Natalia (2024)
The objective of the project proposes to implement adequate public equipment to reduce the current deficit of specialized establishments for the physical development of people with disabilities, thinking about a safe space that generates independence for the user without feeling limits. It is made up of outdoor areas that will function as spaces for sports practice and others for recreation and rest. The proposal has a route that surrounds the entire property, allowing a circulation space where people can use bicycles, walk, run o travel by car that is a proposed internal circulation vehicle to reach spaces and carry out to your sports activities with peace of mind and motivation.........